[Statue of Christopher Columbus, Port of Spain – Trinidad] - (:unkn) unknown (My University, 2010)
This photograph gives a closer, clearer view of the statue of Christopher Columbus upon the monument to Christopher Columbus which is situated in Columbus Square, corner of Independence Square and Duncan Street, Port of Spain. Christopher Columbus was a navigator, explorer, colonizer, who encountered Trinidad in 1498 on his third voyage. This iron statute of Christopher Columbus was a gift from Hippolyte Borde, an affluent local cacao planter and merchant. There are four gargoyles, just under the statue, with open mouths or spouts and basins beneath each. The water from the basins would then overflow into the large round fountain at the base of the monument which is fenced around with chains. Many large drooping trees surround the monument.
Colour: Black and White; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Monuments; Memorials; Statues; Trees; Columbus, Christopher